Bounded generalized random linear operators - Nguyen, Thinh (VNU Journal of Science: Mathematics - Physics; Vol 33 No 3DO - 10.25073/2588-1124/vnumap.4191, 2017)
In this paper we are concerned with bounded generalized random linear operators. It is shown that each bounded generalized random linear operator can be seen as a set-valued random variable. The properties of some special bounded generalized random linear operators are given also. As an application the notion of random resolvent set of a generalized random linear operator is introduced and investigated.